2011
DOI: 10.4236/sgre.2011.24043
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Performance of CIS Photovoltaic Modules under Different Environmental Conditions

Abstract: This work investigates the effects of temperature and radiation intensity on the parameters of a copper indium diselenide (CIS)photovoltaic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The localized defect regions have a larger concentration of traps. When the solar cell is illuminated, the traps are filled and this of course result in increase of leakage current, which means the change in R sh , as seen in Figure b. In addition to these, the current flow patterns and the charge carrier density as well as the imposed voltage distributions under illumination and in the dark conditions are different from each other, which means different series resistance under these two conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The localized defect regions have a larger concentration of traps. When the solar cell is illuminated, the traps are filled and this of course result in increase of leakage current, which means the change in R sh , as seen in Figure b. In addition to these, the current flow patterns and the charge carrier density as well as the imposed voltage distributions under illumination and in the dark conditions are different from each other, which means different series resistance under these two conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed analysis of the generated currents from the CIS module has shown that at low and medium temperatures CIS current ranges at values close to the nominal with a positive short circuit current temperature coefficient 0.15%/ 0 C. This coefficient is equal to the I sc temperature coefficient which can be calculated in Ref [13] for temperatures between 20 and 40 0 C. However over the whole range of working temperature this coefficient remains approximately constant with a slight tendency to decrease. A negative temperature coefficient of the short circuit current is indicated in ref [14].…”
Section: Figure 2 Variation Of the Short Circuit Current Of The Studmentioning
confidence: 85%
“…These include: amorphous silicon (a-Si), cadmium telluride (CdTe), copper indium gallium selenide (CIS or CIGS), dye sensitized solar cells (DSC) and other organic solar cells. Thin film solar cells compared to other solar cells have the highest efficiency of about 12-20% based on Cu (InGa)Se 2 [5].…”
Section: Choice Of Photovoltaic Modulementioning
confidence: 98%
“…Thin film technology offers a number of advantages. Its test sequence for the design qualification and type approval is described in IEC 61646 [5].…”
Section: Introductionmentioning
confidence: 99%